Pengaruh Green Marketing terhadap Minat Menggunakan Layanan Ride-Hailing Ramah Lingkungan dengan Kesadaran Lingkungan sebagai Variabel Moderasi di Kota Yogyakarta. - Tazkia, Indi Hilma (eCo-Buss, 2026)
The expansion of ride-hailing services in Yogyakarta has significantly enhanced urban mobility; however, it has simultaneously contributed to environmental degradation due to intensive fossil fuel usage. As a response to this issue, electric vehicle–based ride-hailing services have been introduced as a more sustainable transportation solution. This study investigates the influence of green marketing on consumers’ intention to use environmentally friendly ride-hailing services, while also examining the moderating role of environmental awareness. A quantitative explanatory research design was adopted, employing Partial Least Squares–Structural Equation Modeling (PLS-SEM) as the analytical method. Data were obtained through an online questionnaire distributed to 100 ride-hailing users in Yogyakarta who satisfied predetermined sampling criteria. Green marketing was operationalized through green product, green price, green place, and green promotion dimensions, whereas intention to use was assessed through repeat intention, referral intention, and preferential intention. The findings demonstrate that green marketing exerts a positive and statistically significant effect on consumers’ intention to use environmentally friendly ride-hailing services. In addition, environmental awareness was found to strengthen the relationship between green marketing and intention to use. These results emphasize the critical role of credible, transparent, and informative green marketing strategies in fostering the adoption of sustainable urban transportation